Fabrication and microstructural studies of porous non-isocyanate polyurethanes (NIPU) and NIPU/POSS hybrid nanomaterials obtained with the particle leaching method - Stachak, Piotr; Korzeniak, Paulina; Hebda, Edyta; Wroński, Sebastian; Tarasiuk, Jacek; Ozimek, Jan; Pielichowski, Krzysztof (Chemical and Process Engineering, 2025)
Non-isocyanate polyurethanes (NIPUs) were synthesised by reacting trifunctional cyclic carbonate with poly(propylene oxide)-derived diamine and further chemically modified with polyhedral oligomeric silsesquioxane (POSS) moieties to obtain NIPU/POSS hybrids. The materials were manufactured in a porous form using sodium bicarbonate in the particle leaching method. FTIR spectra confirmed the creation of urethane groups in the synthesised materials and the incorporation of POSS particles into the NIPU matrix in the reaction between the oxirane rings present in POSS and the used amines. The SEM and computer micro-tomography (—-CT) images obtained confirmed that the use of the selected size of the sodium bicarbonate crystals allowed pores to be obtained with controlled dimensions. The amount of POSS added (5, 10 and 15 wt.%) did not affect the pore size or its shape. Initial submersion studies using Ringer solution to test in vitro biodegradation behaviour show only small fluctuations in pH and conductivity.